2020
DOI: 10.18632/aging.102609
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12p35 deficiency enhances mitochondrial dysfunction and aggravates cardiac remodeling in aging mice

Abstract: Our previous studies have demonstrated that interleukin-12p35 knockout (IL-12p35 KO) regulates the progression of various cardiovascular diseases, such as acute cardiac injury and hypertension. The aims of this study were to investigate whether IL-12p35 KO affects aging-related cardiac remodeling and to explore the possible mechanisms. First, the effects of IL-12p35 KO on heart structure and function were detected, and the results showed that IL-12p35 KO exacerbated cardiac remodeling and increased cardiac sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
14
0
1
Order By: Relevance
“…Antibodies against IL-22 (GeneTex), IL-10R2 (Abcam), IL-22R1 (Santa Cruz), Bax, Bcl2, cleaved caspase-3, extracellular regulated protein kinase (ERK), p-ERK, p38, p-p38, c-Jun N-terminal kinase (JNK), p-JNK, signal transducer and activator of transcription (STAT) 3, p-STAT3, and STAT1 were purchased from Cell Signaling Technology, and antibodies against p-STAT1, STAT5, p-STAT5, p65, and p-p65 were purchased from Abcam. The western blotting was performed according to the methods described in our previous articles [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies against IL-22 (GeneTex), IL-10R2 (Abcam), IL-22R1 (Santa Cruz), Bax, Bcl2, cleaved caspase-3, extracellular regulated protein kinase (ERK), p-ERK, p38, p-p38, c-Jun N-terminal kinase (JNK), p-JNK, signal transducer and activator of transcription (STAT) 3, p-STAT3, and STAT1 were purchased from Cell Signaling Technology, and antibodies against p-STAT1, STAT5, p-STAT5, p65, and p-p65 were purchased from Abcam. The western blotting was performed according to the methods described in our previous articles [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unexpectedly, Yan et al also reported that IL-23 deficiency amplifies the inflammatory response and promotes the release of various inflammatory factors, especially IL-17, which further promotes the infiltration and deposition of gdT cells in the left ventricle, promotes the apoptosis of cardiomyocytes, and aggravates cardiac fibrosis in a murine myocardial infarction model . In addition, IL-12p35 knockout increased the levels of cardiac mitochondrial reactive oxygen species (ROS) and calcium ion overload, which further aggravated mitochondrial dysfunction and energy failure, increased myocardial cell apoptosis, worsened cardiac dysfunction, and increased cardiac fibrosis in 25-month-old aging mice (Ye et al, 2020). However, how the cytokines IL-12 and IL-35 mediate these biological effects is currently unknown.…”
Section: Interleukin-12 Family Members and Cardiac Fibrosismentioning
confidence: 99%
“…However, reducing cardiomyocyte apoptosis can significantly reverse cardiac dysfunction, suggesting that sepsis-induced excessive apoptosis of cardiomyocytes might be the most fundamental cause of cardiac injury [ 36 ]. AIF, which exists mainly in the mitochondrial inner membrane and is less prevalent or nonexistent in the nucleus, is one of the important factors mediating non-Caspase-dependent apoptosis [ 22 ]. Under stimulation by external pathological factors, AIF is released in massive quantities by mitochondria and transferred to the nucleus through the cytoplasm [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria were isolated from the left ventricle (LV) using a mitochondrial isolation kit (Cayman) as described in our previous study [ 22 ]. In brief, fresh LV tissue was lysed using a mitochondrial separation solution and then centrifuged at 700 × g for 10 minutes.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation